Systematic Review of Technology-Based Interventions Targeting Chronically Ill Adults and Their Caregivers. (November 2020) - Irani, Elliane; Niyomyart, Atsadaporn; Hickman, Ronald L.
The purpose of this systematic review is to synthesize the study design features as well as the attributes and outcomes of technology-based health interventions targeting chronically ill adults and their family caregivers. Twenty papers representing 19 studies met the inclusion criteria. Various theoretical foundations or approaches guided the interventions in 11 studies. Interventions either aimed to support patient self-management and improve patient outcomes or enhance shared illness management and improve patient and caregiver outcomes. The interventions included educational, behavioral, and support components and were delivered using various technologies ranging from text messaging to using the Internet. Overall, patients and caregivers expressed improvements in self-management outcomes (or support) and quality of life. Interventions with a dyadic focus reported on interpersonal outcomes, with improvements noted mostly in patients. This review captures an emerging area of science, and findings should be interpreted in light of the methodological limitations of the included studies.